Competitividade internacional e a criação de um ambiente que a favoreça - Velloso, João Paulo dos Reis (Nova Economia, 2013)
<!–[if gte mso 9]> Normal 0 21 MicrosoftInternetExplorer4 <![endif]–> Competitividade internacional e a criação de um ambiente que a favoreça <!–[if gte mso 10]> <![endif]–>